2000
DOI: 10.1007/s001480050136
|View full text |Cite
|
Sign up to set email alerts
|

Fertility assimilation of immigrants: Evidence from count data models

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 15 publications
7
74
1
4
Order By: Relevance
“…Results showed, in line with the literature (e.g., Kane 1986), that women with an urban background have significantly lower transition rates both to a first and to a second birth. The religious affiliation has one category with a significant effect on second births, i.e., having no religious affiliation was found to have a birth-risklowering impact (e.g., Mayer and Riphahn 2000). In general, this probably reflects more of the variability within the West German group than differences between immigrants and Germans; for immigrants there appears to be a relatively high association between country background and religion.…”
Section: Model 14mentioning
confidence: 98%
See 1 more Smart Citation
“…Results showed, in line with the literature (e.g., Kane 1986), that women with an urban background have significantly lower transition rates both to a first and to a second birth. The religious affiliation has one category with a significant effect on second births, i.e., having no religious affiliation was found to have a birth-risklowering impact (e.g., Mayer and Riphahn 2000). In general, this probably reflects more of the variability within the West German group than differences between immigrants and Germans; for immigrants there appears to be a relatively high association between country background and religion.…”
Section: Model 14mentioning
confidence: 98%
“…Given that fertility patterns vary between the regions of origin and destination, a convergence may be achieved within some years of residency (shown by Iutaka et al 1971;Rindfuss 1976;Bach 1981;Farber and Lee 1984;Hervitz 1985;Nauck 1987;Ford 1990;Ram and George 1990;Schoorl 1995;Mayer and Riphahn 2000;Milewski 2007). This resemblance may be triggered by two primary channels: cultural factors and/or socio-economic conditions.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…This increases the importance of stable employment to avoid financial difficulties and social stigma (Brand and Thomas 2014). Among immigrants in Germany, age at parenthood is also lower, and the number of children is higher (Mayer and Riphahn 2000). As a result, immigrants are more likely to lose their jobs in a life stage that is particularly vulnerable to the adverse effects of unemployment.…”
Section: Compositional Differencesmentioning
confidence: 99%
“…The results of studies on outcomes other than infant mortality support the assimilation theory. For example, a number of studies have found that female labour force participation and fertility converge towards non-immigrant levels with length of stay (Antecol 2000;Mayer and Riphahn 2000). In this paper we will study the assimilation process more closely.…”
Section: Introductionmentioning
confidence: 99%